Option-like Behavior of Value Strategies in Bear Markets – Evidence from the US Stock Market - Ruokoja, Lasse (My University, 2018)
Value investing is an investment paradigm according to which value stocks earn higher returns than growth stocks. The value premium (the outperformance of value stocks over growth stocks) has been documented in numerous academic studies worldwide and it has become one of the most famous stock market anomalies. The purpose of this thesis is to extend the academic literature by investigating whether four different value strategies based on one-dimensional valuation ratios (B/M, D/P, CF/P and E/P) are subjects to option-like behavior in bear markets. This is done via the methodology of Daniel and Moskowitz (2016). This study includes data from the US stock market over the periods of 07/1928–06/2017 (B/M and D/P portfolios) and 07/1951–06/2017 (CF/P and E/P portfolios). According to the results, the zero-cost value-minus-growth strategies (strategies that buy value deciles and sell growth deciles) also display option-like behavior in bear markets. Interestingly, the strategies formed on B/M and D/P ratios are long call options whereas the strategies formed on CF/P and E/P ratios are short call options on the stock market in bear markets. Since the returns of the VMG strategies are positively correlated with each other when the sample period is equal (07/1951–06/2017), it can be speculated that the option-like behavior (as long call options) is presumably driven by stock market comovements during and aftermath the Great Depression in the 1930s.
Keywords: Stock market; asset pricing; value investing; valuation ratios; optionality; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|